Punitive Hetero-Evaluation of Teacher Performance in the Post-Truth Era: A Critical Analysis - Richard, Enrique (2025)
In Bolivia and Ecuador, there is consensus in considering hetero-evaluation as Teaching Performance Assessment (TPA) by the principals who receive the teaching activity, the students. Consequently, this paper analyzes the epistemological, historical, psychosocial, and legal context of TPA in Bolivia and Ecuador. Currently, students hold the power to determine teacher tenure through TPA. The psychosocial profile of students during the 1918 reform is compared with those of today. It is argued and demonstrated that in the post-truth sociocultural context, students behave like adolescents with limited and restricted ethical and moral values, consistent with a subjective perception of their narcissistic, presentist, superficial, nomophobic, and anti-intellectual profile; they lack self-criticism, critical thinking, empathy, authenticity, otherness, self-esteem, and responsibility; they are incapable of making important decisions, sensitive, anxious, and have limited autonomy, limited language, unclear sexuality, and limited cultural knowledge. They are adolescents whose goal is to pass, not learn. It is evident that they lack the knowledge and skills they are intended to assess, violating the epistemic principle of academic peers. The teacher-student relationship compromises the objectivity of the process. It is concluded that TPA in the current context is a paradoxical fallacy, without any epistemological basis to justify it.